(untitled) (Research, Society and Development, 2022)
The environmental conservation of natural resources with tourist potential and maintenance of ecological services is something difficult to value, due to the individual economic interests of the development process. Among these spaces is the Uirapuru Municipal Natural Park, in the municipality of Nova Lacerda, Mato Grosso. It is an area of important environmental value, both for the maintenance of biodiversity and for the practice of ecological tourism. This research sought to instigate the environmental and economic importance of the presence of the park and to propose initiatives for the use of space and strategies for the conservation of the place. The methodological steps involved bibliographic analysis and search for data from the municipality of Nova Lacerda, as well as scenarios were developed that denote the environmental valuation of the park. The research creates scientific subsidies for discussions of environmental policies for the conservation process of the park area, denoting its importance in the economic context of the municipality, as well as serving as a model to subsidize replications in other natural parks.